2021
DOI: 10.1093/ofid/ofab517
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the inFLUenza Patient-Reported Outcome Plus (FLU-PRO Plus) Instrument in Patients With Coronavirus Disease 2019

Abstract: Background The FLU-PRO Plus is a patient-reported outcome data collection instrument assessing symptoms of viral respiratory tract infections across eight body systems. This study evaluated the measurement properties of FLU-PRO Plus in a study enrolling individuals with COVID-19. Methods Data from a prospective cohort study (EPICC) in US Military Health System (MHS) beneficiaries evaluated for COVID-19 was utilized. Adults wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Viral respiratory illnesses are common, although the symptoms, symptom intensity, and symptom duration can vary across illnesses [28,31]. The onset of the novel coronavirus (COVID-19) brought about a variety of patient-reported surveys that individuals could use to report and track their symptoms [33][34][35][36]. FLU-PRO© is a validated PROM originally developed to standardize capture of patients' symptoms associated with influenza, respiratory syncytial virus, rhinovirus, enterovirus, and endemic coronaviruses throughout a 14-day course, or until symptoms subside and participants return to their baseline health [28,31].…”
Section: Introductionmentioning
confidence: 99%
“…Viral respiratory illnesses are common, although the symptoms, symptom intensity, and symptom duration can vary across illnesses [28,31]. The onset of the novel coronavirus (COVID-19) brought about a variety of patient-reported surveys that individuals could use to report and track their symptoms [33][34][35][36]. FLU-PRO© is a validated PROM originally developed to standardize capture of patients' symptoms associated with influenza, respiratory syncytial virus, rhinovirus, enterovirus, and endemic coronaviruses throughout a 14-day course, or until symptoms subside and participants return to their baseline health [28,31].…”
Section: Introductionmentioning
confidence: 99%
“…Symptom burdens not significant at 0.007 were Chest/Respiratory ( p = 0.024), Gastrointestinal ( p = 0.124), and Smell/Taste ( p = 0.032) domains, although they declined suggestively much faster with TQF therapy. FLU-PRO plus is a reliable self-administered SARS-CoV-2 symptom scoring system that has been validated and suggested as a tool to compare results from different studies of viral pulmonary infections [ 10 ]. Indeed, with the advent of multiple trials for SARS-CoV-2 therapeutics, patient-reported quality of life as a core outcome measure was recommended by the Global SARS-CoV-2 Core Outcomes Set (SARS-CoV-2 COS) initiative [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…FLU-PRO plus is a reliable self-administered SARS-CoV-2 symptom scoring system that has been validated and suggested as a tool to compare results from different studies of viral pulmonary infections [ 10 ]. Indeed, with the advent of multiple trials for SARS-CoV-2 therapeutics, patient-reported quality of life as a core outcome measure was recommended by the Global SARS-CoV-2 Core Outcomes Set (SARS-CoV-2 COS) initiative [ 10 ]. Our paper validated the Modified FLU-PRO Plus questionnaire as a SARS-CoV-2 symptom tool as it focuses on what is clinically relevant to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Weekly check-ins were conducted telephonically or using internet-based communication systems to assess for COVID-19–related symptoms. Secondary endpoints included symptoms assessed through FLU-PRO Plus (successfully used in other COVID-19 studies) [ 14–16 ]. Multiple, discrete occurrences of COVID-19 infection could be identified in a single participant.…”
Section: Methodsmentioning
confidence: 99%